Domestic energy demand assessment of coastline rural communities with solar electrification. (1st January 2017) - Diemuodeke, E. O.; Addo, A.; Dabipi-Kalio, I.; Oko, C. O. C.; Mulugetta, Y.
ABSTRACT: The coastline rural communities in the Niger Delta region of Nigeria have long suffered from the consequences of poor rural electrification, environmental degradation, and health challenges. There is an urgent need to provide an optimal sustainable and environment-friendly energy system for the coastline rural communities in Nigeria, which has the potential of ameliorating the climate change in this country. The HOMER hybrid optimization software and the estimated domestic energy demand of the coastline rural communities were used to determine the best PV solar energy system. The NASA SEE database with monthly averaged values for global horizontal radiation over a 22-year period was considered in the current analysis. The daily energy demand of a typical household in the communities was estimated for the existing energy demand (EED), future electric energy demand (FEED), and future base energy demand (FBED) scenarios as 5.640, 8.830, and 7.233 kWh, respectively. The suggested best energy system has a cost of electricity of 0.651, 0.653, and 0.674 $/kWh for the EED, FEED, and FBED, respectively. The best energy system gives the best components with an appropriate operating strategy to provide an efficient, reliable, cost-effective, and environment-friendly system. It is shown that both positive energy policies of the Federal Government of Nigeria toward renewable energy penetration and the support from the oil-producing companies toward their operational areas would see the cost of electricity being significantly reduced. It is envisaged that the implementation of the suggested energy system with other environmentally responsible interventions would support the Niger-Delta's coastline rural communities, whose livelihoods have been impaired by gas and oil exploration, to attain their full environmental and socioeconomic potentials.